Yrkesgruppers anspråk på arbetet med barn i behov av särskilt stöd - Petra Gäreskog (Educare)
This study aims to illuminate preschool teachers describe which occupational groups – preschool teachers and special educational needs coordinators (SENCOs) – claim jurisdiction (i.e. the area that the professional group controls) over the work with children in need of special support. The data consist of interviews with 15 preschool teachers. The analysis is based on Abbott's (1988) division of professional work into three aspects: a) formulation of a problem b) reasoning about the problem and c) treating the problem. One area where preschool teachers claim jurisdictional control is related to the formulation of the problem. When it comes to the aspect of the professional work which concerns reasoning about the problem, the preschool teachers report that SENCOs claim jurisdictional control instead. The results show a less straightforward image of the treatment of the problem. Preschool teachers sometimes report themselves to claim jurisdictional control over treatment and other times report that SENCOs have jurisdiction over the treatment of the problem. In the discussion, jurisdiction is related to the various aspects of professional work with children in need of special support and the issue of inclusion. The fact that SENCOs seem to have a strong jurisdiction over treatment and expert knowledge of children’s perceived shortcomings could contribute to the preschool teachers renouncing responsibility for children in need of special support. Another conclusion is that preschool teachers need to be strengthened in their professional roles and that increased special educational knowledge could contribute to preschool teachers feeling more secure in their professional roles and thus are able to meet all children’s needs in preschool.